PENGARUH DARING DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA - Muh Fahrurrozi; Agus Riswanto; Irda Nur Oktafiani (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
This study aims to determine the effect of online learning motivation on student achievement at SMK Negeri 2 Selong during the Covid-19 pandemic. This research uses quantitative methods. Research data collection techniques using a questionnaire. The research sample was 53 students of SMKN 2 Selong using purposive sampling technique. The analytical tool used is multiple linear regression model. Based on the results of multiple linear regression analysis with an online coefficient value of 0.778 indicating a positive influence and a learning motivation regression coefficient value of 0.078 indicating a positive influence. While the results of the partial analysis show that the online significance value on learning achievement is 0.00 < 0.05 and the t-count value is 6.930>2.00, the significance value of learning motivation on learning achievement is 0.00 < 0.05 and the t-count value is 3.977 > 2.00, partially showing that there is a significant effect. So the results of this study indicate that there is a positive and significant influence between online and learning motivation partially on student achievement.